Effects of river discharge and tidal meandering on morphological changes in a meso tidal creek. (5th March 2020) - Wang, Xianye; Sun, Jianwei; Zhao, Zhonghao
Abstract: A tidal creek represents a typical morphologic unit in an intertidal flat. The development and migration of a tidal creek can affect the mass transport, ecological environment, and geomorphologic evolution of the flat. By using field observations, this study links hydrodynamics, sediment transport processes with short-term changes in topography at a typical tidal creek system located at the Chongming Island of the Yangtze River estuary. Hydrodynamic and sediment transport associated with varying tidal cycles across both wet (flood) and dry seasons were measured through the field campaign. The wet and dry seasons represent higher and lower discharges of Yangtze River, respectively. The results indicated that most of the suspended sediment becomes entrained at the beginning of a flood tide. At a fixed point, 7.2 times of suspended sediments, which were entrained out of the creek in wet season, began to be transported along the creek compared to dry season. In the dry season, high flow velocity and shear stress conditions occurred in the tidal creek because the water level was below the top of the flat. In summary, the tidal creeks were found to serve as effective conduits for the transportation of sediments in the wet season, and the secondary flow enhanced the development of tidal meandering. Seasonal variations in creek morphological changes were also continuously monitored over two years at intervals of two months. The change of creek morphology varied from the high level to low level, and tidal meandering was strongly associated with flood and ebb tides. Highlights: Water flow and sediment transport were studied in a meso tidal creek system. The tidal flat tended to receive sediment deposits from April to October, and to be eroded in the other months. Tidal creek morphology was stable at the high creek level, and it meandered at the low level. The results contribute to a better understanding of the development mechanism of tidal creeks.